SOME INFORMATION ON THE CULTIVATION AND TRADE OF KARAKUL FUR IN BUKHARA EMIRATE (Scientific journal of the Fergana State University, 2024)
This article provides detailed information that in the late XIX – early XX century, during the development of entrepreneurship and the expansion of the layer based on private property in the Bukhara Emirate, the collection and preparation of karakul skins for sale abroad was in the hands of large entrepreneurs. In particular, it was noted that the Bukhara Emirate was the leader in breeding the Karakul sheep breed all over the world, obtaining Karakul furs was the main source of income, and the skins of Karakul sheep were highly valued in the markets of Russia and Europe.